2013
DOI: 10.1155/2013/616737
|View full text |Cite
|
Sign up to set email alerts
|

Carica papayaLeaves Juice Significantly Accelerates the Rate of Increase in Platelet Count among Patients with Dengue Fever and Dengue Haemorrhagic Fever

Abstract: The study was conducted to investigate the platelet increasing property of Carica papaya leaves juice (CPLJ) in patients with dengue fever (DF). An open labeled randomized controlled trial was carried out on 228 patients with DF and dengue haemorrhagic fever (DHF). Approximately half the patients received the juice, for 3 consecutive days while the others remained as controls and received the standard management. Their full blood count was monitored 8 hours for 48 hours. Gene expression studies were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
144
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(152 citation statements)
references
References 11 publications
6
144
1
1
Order By: Relevance
“…ALOX 12 gene is known to be associated with increased megakaryocyte production as well as its conversion to platelets through 12-HETE mediated pathway which in turn leads to increased platelet production. 17 The present study, for the first time, evaluates the comparative increasing platelet effect of freshly prepared leaf concentrate of Carica papaya and hydrocortisone in induced thrombocytopenic rats. This was an important therapeutic investigation as there is no effective treatment method for thrombocytopenia at present.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…ALOX 12 gene is known to be associated with increased megakaryocyte production as well as its conversion to platelets through 12-HETE mediated pathway which in turn leads to increased platelet production. 17 The present study, for the first time, evaluates the comparative increasing platelet effect of freshly prepared leaf concentrate of Carica papaya and hydrocortisone in induced thrombocytopenic rats. This was an important therapeutic investigation as there is no effective treatment method for thrombocytopenia at present.…”
Section: Discussionmentioning
confidence: 98%
“…The veins and the petiole of the Carica papaya leaves selected for the tests was removed and Juice was extracted from fresh leaves using a juice extractor without any addition of water, under sterile conditions and the mucilaginous (with mucus) juice concentrate manually was separated (like squeezing coconut milk) from the leaf-residue. 17 Then the mixture was filtered to obtain a pure extract of Carica papaya leaves. Finally, the volume of the extract was measured and the extracts were stored at 4°C until use and administered orally 2ml/day per rat.…”
Section: Preparation and Dosage Of Carica Papaya Leaf Juicementioning
confidence: 99%
“…A total of 229 patients were recruited (111 and 117 patients were from the interventional and control group respectively) whereby the experimental subject were given fresh juice from 50 grams of C. papaya leaves once daily, 15 minute after breakfast for 3 consecutive days. The findings has shown a significant increase in platelet count in the intervention group after 40 hours and 48 hours of treatment (Subenthiran et al, 2013). Furthermore, in Karachi, Pakistan a case report showed that a medical student with symptom of DF was given 150mL of papaya leaf extract once daily for 5 consecutive days and a continuous rise in platelet by the end of the fifth day was recorded (Siddique et al, 2014).…”
mentioning
confidence: 99%
“…For centuries Carica papaya leaves obtained from papaya tree have been used in the folk medicine to combat DF, because it is considered to be an effective, safe and cheap remedy (Dharmarathna et al, 2013;Subenthiran et al, 2013). Many studies have revealed that C. papaya leaves has a lot of benefits such as anti-inflammatory agent, antitumor, antioxidant, nephroprotective, hepatoprotective, hypoglycemic, hypolipidaemic, anti-sickling properties in sickle cell disease and act as a vermifuge (Patil et al, 2013;Subenthiran et al, 2013 Siddique et al, 2014). Due to its' ability to exert therapeutics effects on human; numerous studies on C. papaya leaf have been conducted in order to evaluate its properties, safety and toxicity in human.…”
mentioning
confidence: 99%
See 1 more Smart Citation